Modeling climate analogues of climate smart village sites in West and Central Africa: Case Study from Benin, Burkina Faso, Mali, Niger, and Tchad - Ogou, Anani; Singh, Manjari; Kagabo, Desire M; Ouedraogo, Mathieu; Laderach, Peter (2024)
As part of the TARSPro Programme, the Alliance of Bioversity and ClAT is supporting the West and Central African Council for Agricultural Research and Development (CORAF) in implementing the Climate Smart Agriculture (CSA) approach in Benin, Burkina Faso, Mali, Niger and Chad through the Climate Smart Village (CSV) approach. The aim is to scale up CSA practices, innovations, and technologies in west and central Africa region at rural community’s level. This necessarily involves a scientific approach developed by CIAT, which consists of modelling the climatic analogues of the CSV sites identified, so to implement on the ground the farm of future (FoF) approach that will enable the rural and farming communities of these 5 pilot villages, namely Worogui-Goura in Benin, Ouda in Burkina Faso, Sabénébougou in Mali, Kiéché in Niger, and Tambling in Chad, to take advantage of climate resilience options. This poster was produced and presented during the joint supervision mission of the donors (CORAF & Confédération Suisse). It shows the areas with similar future climate characteristics to the 5 CSVs.